Diversity and inclusion have greater support than most Americans think - Naomi Isenberg; Markus Brauer (Scientific Reports)
Abstract In a series of large-scale studies (N = 5,448) we show that Americans across many different demographic categories vastly underestimate their fellow Americans’ support for diversity and inclusion. Trump voters were particularly inaccurate when their task was to estimate prevalent attitudes among Biden voters. Our results show that the degree of underestimation of others’ support for diversity and inclusion predicts the frequency of conversations about diversity, reduced intentions to behave inclusively, and a smaller likelihood of confronting discrimination. Our last two studies (N = 723) demonstrate that it is possible to correct people’s misperceptions through “social norms messaging,” i.e., communications about statistics from national opinion polls highlighting that a majority of Americans are pro diversity. Our findings suggest that once people form accurate impressions of the high percentage of Americans who support diversity and inclusion, they will be more likely to be in favor of pro-diversity initiatives, behave more inclusively, and endorse policies aimed at reducing racial disparities.